Areli es una dreamer : una historia real - Morales, Areli (Random House Studio, 2021)
"In the first picture book written by a DACA dreamer Areli Morales tells her own powerful and vibrant immigration story of moving from a quiet town in Mexico to the bustling and noisy metropolis of New York City"--